An integrated marketing communications campaign for Travel Lab Philippines - Catan, James Christian A. (Animo Repository, 2014)
Travel Lab Philippines was established in 2012, offering travel packages initially to three destinations in Luzon. In 2014, the partnership has changed hands and is now embarking on expanding the destinations offered and capturing a piece of the growing domestic tourism market. The vision of promoting the Philippines and helping the young Filipinos see and understand their own country is the reason why Travel Lab focuses on the adventure travelling segment. The tour packages offered already includes the land transportation to and from Manila, tour entrance & environmental fees, a travel coordinator with them all the time, tour guides and lodging/accommodations. Currently offered destinations are Ilocos, Mount Pulag and Sagada. Selling is done mostly through online and social media means, as Travel Lab does not keep a brick and mortar office to lower costs. Domestic tourism has been growing in double-digits for the past three years, and is forecasted to maintain the pace for the next three years. Government efforts in promoting in-bound (foreigners) tourism has had a massive halo-effect in the local market, which was also helped by the increasing disposable income by Filipinos due to stable and economic growth. Given the scenario, we want to reach out to the demographic young professionals, aged 25-35 male and female, residing in Metro Manila and the nearby suburbs. They are Millennials, mostly single and multitask in and out of the office. They have money to spend for travelling and but time-poor and can only go out during weekends. The growth of the industry has not gone unnoticed, and there is an influx of travel agency-tour operator hybrids in the market using also the internet as their channel to talk to customers. The domestic travel market is currently diverging into polar opposites, with the industry segmenting its offerings by focusing either in the luxury or economy segment. Travel Labs packages in effect are becoming generic at the eyes of the consumer, and with the on-going price wars in the economy segment, the market is using price as their decision factor. Based on the market and the current status of the company, we would like to do two things: (1) reposition Travel Lab to get out of the current price wars enveloping the economy segment, (2) create a communication plan that will create organic reach.